Dorang (Dolan Semarang) Game Solution to Introduce Semarang Municipality and Semarang Regency as Tourist Attraction - Lidya Oktorina Kusuma Sakti; Brenda Chandrawati (SISFORMA, 2016)
Abstract- Tourism is the departure of a person in a short period of time into a tourism site with the intention to relax and refresh the mind. Tourism will feel convenient if visiting the tourism site that have fun attractions. One of the city that has many attractions is Semarang city and Semarang regency. Semarang city and Semarang regency has a natural attractions, social and culture, travel games, agro tourism, and culinary tours. According to a study, 64% of 30 respondents who are domestic travelers from 15-30 years old, did not know the information of locations from the tourism site in Semarang city and Semarang regency. With the little knowledge from domestic travelers, DORANG (Dolan Semarang) is made so that this game can be used as a guide to travel and as a media promotion of these attractions. This game contains travel map of Semarang city and Semarang regency along with the information of tourism sites. After respondents are finished playing this game, they will be known better about the information of tourism sites in Semarang city and Semarang regency and also more recognizing these attractions.